A bimetallic catalyst prepared with a complexing agent containing only hydroxyl functional groups, and a method for preparing and using the same
Patent Information
- Application Number
- CN202610792410.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-09
AI Technical Summary
铜基催化剂因其较强的氢活化能力,难以达到较高的乙醇酸甲酯选择性,而银基催化剂面临着金属负载量高,催化剂易烧结失活的问题
1.本发明不仅是筛选络合剂种类,而是关注络合剂分子尺寸、羟基添加量及分布的特点,能够更加有效地调控银离子的络合行为以及核壳结构的形成。当采用分子尺寸较小且羟基添加量适宜的乙二醇络合剂体系时,银离子能够被适度络合并迁移至铜表面,从而形成更完整、更均匀的银壳层,提高Cu@Ag核壳结构的完整性和稳定性。在相同羟基添加量条件下,本发明验证了因分子尺寸和羟基分布差异而导致的银离子还原置换行为的不同,避免仅以羟基添加量判断络合效果。
Smart Images

Figure CN122875246A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology, and relates to Cu@Ag / SiO2 bimetallic catalysts based on the synergistic regulation of complexing agent molecular size, hydroxyl addition amount and distribution. Specifically, it is a bimetallic catalyst prepared with a complexing agent containing only hydroxyl functional groups, its preparation method and application. Background Technology
[0002] Methyl glycolate (MG), as an important fine chemical intermediate, possesses the chemical properties of both alcohols and esters. It can participate in various chemical reactions such as transesterification, condensation, and hydrogenation, demonstrating broad application potential in pharmaceutical intermediates, pesticides, and organic synthesis. Especially against the backdrop of increasing emphasis on sustainable development, my country's domestic demand for biodegradable materials is projected to reach 4.28 million tons by 2030. Therefore, the market demand for polyglycolic acid (PGA), a biodegradable material and a downstream product of MG, is surging, making the development of efficient, low-cost, and sustainable MG synthesis routes of significant strategic importance.
[0003] Based on my country's resource endowment, developing coal-based process routes to selectively hydrogenate dimethyl oxalate to produce methyl glycolate can not only effectively solve the problems of harsh reaction conditions and serious pollution associated with traditional routes such as chloroacetic acid hydrolysis and formaldehyde carbonylation, but also promote the transformation of coal into high-value-added fine chemicals. This is an important way to optimize my country's energy structure and achieve the clean utilization of coal.
[0004] In this process route, the preparation of a highly efficient and stable hydrogenation catalyst is the core and technical challenge for achieving large-scale industrial production. Copper-based catalysts, due to their strong hydrogen activation ability, struggle to achieve high selectivity for methyl glycolate, while silver-based catalysts face the problem of high metal loading and easy sintering and deactivation. Therefore, preparing Cu@Ag / SiO2 core-shell catalysts using a reduction-replacement method is an effective approach to reduce silver loading while maintaining catalyst activity and stability. Existing techniques typically focus on whether and what type of complexing agent is added, but pay insufficient attention to the molecular size, hydroxyl distribution, and amount of complexing agent added, which are closely related to the formation of the catalyst structure. Therefore, it is necessary to provide a method for preparing Cu@Ag / SiO2 bimetallic catalysts based on the synergistic regulation of complexing agent molecular size, hydroxyl addition amount, and distribution. Summary of the Invention
[0005] The purpose of this invention is to address the core technology of catalyst preparation in the hydrogenation of dimethyl oxalate to methyl glycolate, providing a copper-silver bimetallic catalyst and its preparation method that differs from the conventional method of "simply adding a complexing agent". The complexing agent control factors are further refined into the molecular size of the complexing agent, the amount and distribution of hydroxyl groups, and the complexing strength of silver ions, the diffusion behavior of silver ions to the copper surface, and the reduction process of silver species on the copper surface are synergistically controlled by both. This results in a Cu@Ag / SiO2 bimetallic catalyst with a more uniform silver shell, stronger intermetallic interaction, and better catalytic performance.
[0006] The core technical solution adopted in this invention is: A bimetallic catalyst prepared using a complexing agent containing only hydroxyl functional groups includes a support and an active component, wherein the active component is a copper species and a silver species, and the support is silica; the silver species accounts for 1-10 wt.% of the total mass of the catalyst, and the copper species accounts for 1-10 wt.% of the total mass of the catalyst; a copper silicate precursor is prepared by ammonia stripping, and the reduced precursor, silver ammonia solution, and complexing agent are mixed and treated to obtain the finished catalyst; the complexing agent can complex silver ions, thereby regulating the rate of the electrochemical displacement reaction, and the complexing agent is ethylene glycol.
[0007] In the bimetallic catalyst, silver species account for 1-10 wt.% of the total mass of the catalyst, preferably 4-7 wt.%; copper species account for 1-10 wt.% of the total mass of the catalyst, preferably 7-10 wt.%. The catalyst has a specific surface area of 50-300 m² / g, an average pore size of 5.0-15.0 nm, and an average pore volume of 0.3-1.7 cm³ / g; the copper-silver bimetallic particle size is 1.0-12.0 nm, preferably 3.0-8.0 nm.
[0008] The complexing agent is a complexing agent containing only hydroxyl functional groups. The hydroxyl-containing complexing agent coordinates with silver ions through hydroxyl groups, thereby reducing the random reduction and self-nucleation tendency of silver ions and regulating the reduction and replacement behavior of silver ions on the copper surface.
[0009] The catalyst has the following structure: silver species are coated on the surface of a copper core in the form of a shell, forming a core-shell structure; the core-shell structure is located on a support of silica in the form of particles, wherein strong interactions are formed between the metals and between copper and silica. The complexing agent has the characteristics of small molecular size, moderate amount of hydroxyl groups, and dispersed spatial distribution of hydroxyl groups, which is a complexing agent system that is conducive to the complexation and migration of silver ions.
[0010] The aforementioned "molecular size" refers to the spatial volume and chain length of the complexing agent molecule. Smaller molecular sizes of hydroxyl-containing complexing agents make it easier for them to carry silver ions and diffuse to the copper surface to undergo reduction and displacement reactions; although larger molecular sizes of complexing agents may have a stronger silver ion complexing ability, they are prone to forming steric hindrance after adsorption on the copper surface, which hinders the migration of silver ions to the copper surface, resulting in the misplaced deposition of some copper species on the carrier.
[0011] The aforementioned "hydroxyl group addition amount" refers to the total amount of hydroxyl groups involved in the silver ion complexation in the preparation system. When the hydroxyl group addition amount is too low, the complexing effect of the complexing agent on silver ions is insufficient, and silver ions are prone to rapid reduction or self-nucleation, resulting in silver species not being uniformly coated on the copper surface. When the hydroxyl group addition amount is appropriate, silver ions are moderately complexed and can be uniformly deposited on the copper surface while maintaining diffusion ability, forming a continuous and uniform silver shell layer. When the hydroxyl group addition amount is too high, the complexing agent residue and excessive adsorption may block the carrier pores or cover the copper surface to form steric hindrance, which will reduce the uniformity of the silver shell layer.
[0012] The aforementioned "hydroxyl distribution" refers to the relative position and dispersion state of hydroxyl groups in the complexing agent molecule. When the hydroxyl distribution is too concentrated or restricted by molecular conformation, the proportion of hydroxyl groups that can effectively participate in the complexation of silver ions decreases; when the hydroxyl distribution is too dispersed and the molecular chain is too long, the binding of the complexing agent with silver ions may cause the silver ions to move away from the copper surface, reducing the coating efficiency of silver on the copper surface.
[0013] Another object of the present invention is to provide a method for preparing the above-mentioned bimetallic catalyst, comprising the following steps: (1) Preparation of copper silicate precursor: copper salt is fully dissolved in deionized water and then a certain volume of ammonia water is added to form a copper ammonia solution; silica sol is added dropwise under mechanical stirring, and after aging treatment, the temperature is raised to evaporate ammonia. After the pH drops to 6-7, the product is filtered, washed, dried and calcined to obtain copper silicate precursor.
[0014] (2) Reduction treatment: The copper silicate precursor obtained in step (1) is reduced in a hydrogen atmosphere, preferably at 250-350℃ for 2-6 h.
[0015] (3) Reduction and displacement: Under an inert atmosphere and in the dark, the reduced copper silicate precursor obtained in step (2) is dispersed in deionized water, and silver salt solution and hydroxyl complexing agent are added and mechanically stirred to mix and react.
[0016] (4) Post-treatment: The mixture obtained in step (3) is washed with a large amount of deionized water and then dried at 80-130℃ for 12-24 h to obtain Cu@Ag / SiO2 catalyst based on the synergistic regulation of complexing agent molecular size, hydroxyl addition amount and distribution.
[0017] In step (1), the aging time is 4 h and the ammonia stripping temperature is 80℃; in step (3), the amount of silver nitrate added is to ensure that the copper-silver mass ratio is 3:2, the concentration of the complexing agent can be adjusted according to the amount of silver ions added and the amount of target hydroxyl added, the complexing agent is ethylene glycol, the mixing reaction time is 30 min-60 min, and the ambient temperature is 0℃. The catalyst described in this invention can be used for the selective hydrogenation of dimethyl oxalate to methyl glycolate. Specifically, the Cu@Ag / SiO2 bimetallic catalyst is packed into a fixed-bed reactor and reduced under a hydrogen atmosphere at 225°C. Gasified dimethyl oxalate is then introduced and mixed with hydrogen to carry out the reaction. The reaction pressure is 0.5-3.5 MPa; the reaction temperature is 200-250°C; and the mass hourly space velocity (HSV) of dimethyl oxalate is 0.1-6.0 h⁻¹. -1 The hydrogen-ester molar ratio is 60-140.
[0018] The present invention has the following beneficial effects: 1. This invention not only screens complexing agents but also focuses on the characteristics of complexing agent molecular size, hydroxyl group addition amount, and distribution, enabling more effective control of silver ion complexing behavior and core-shell structure formation. When using an ethylene glycol complexing agent system with smaller molecular size and appropriate hydroxyl group addition, silver ions can be moderately complexed and migrated to the copper surface, thereby forming a more complete and uniform silver shell layer, improving the integrity and stability of the Cu@Ag core-shell structure. Under the same hydroxyl group addition conditions, this invention verifies the differences in silver ion reduction and replacement behavior caused by differences in molecular size and hydroxyl group distribution, avoiding the need to judge the complexing effect solely based on the amount of hydroxyl group addition.
[0019] 2. This invention can reduce the problems of independent nucleation, local aggregation, or misaligned deposition of silver species on the support, improve the integrity of the Cu@Ag core-shell structure, enhance intermetallic interactions, increase the electron density of silver and the hydrogenation capacity of the catalyst, and improve the conversion rate of dimethyl oxalate while maintaining the selectivity of methyl glycolate.
[0020] 3. By avoiding excessive complexing agent residue and pore blockage, this invention can reduce the tendency for side reactions to occur and reduce the formation of byproducts such as dimethyl ether, which is beneficial to improving the yield of methyl glycolate and the quality of subsequent products. Attached Figure Description
[0021] Figure 1 The molecular structural formulas of the complexing agents in the comparative examples and embodiments of this invention are shown below; Figure 2 The images show the HAADF-STEM and particle size distribution of the comparative and experimental samples in this invention.
[0022] Figure 3This is a schematic diagram illustrating the synergistic regulation of silver ion complexation and Cu@Ag structure formation by the molecular size, amount and distribution of the complexing agent in this invention. Detailed Implementation
[0023] The present invention will be further described below through embodiments, but is not limited to these embodiments. Experimental methods not specifically described in the embodiments generally use conventional conditions and conditions described in manuals, or conditions recommended by the manufacturer. The general equipment, materials, reagents, etc., used are all commercially available unless otherwise specified.
[0024] The methods for online reduction and catalytic activity evaluation of the catalyst in this embodiment and comparative example are as follows: In this invention, the hydrogenation reaction of dimethyl oxalate is carried out in a fixed-bed reactor. 0.5 g of catalyst is loaded and reduced at 225°C in a hydrogen atmosphere at 2.5 MPa with a gas flow rate of 30 mL / min for 4 h. Subsequently, the dimethyl oxalate / methanol feedstock is vaporized and mixed with hydrogen before entering the reaction system, with a hydrogen-to-ester ratio of 80. The hydrogenation reaction is then carried out at 2.5 MPa and 225°C. The products after the reaction are analyzed by gas chromatography, and the conversion rate of dimethyl oxalate and the selectivity of methyl glycolate, ethylene glycol, and other byproducts are calculated. Since the hydrogenation reaction of dimethyl oxalate is a series reaction, and methyl glycolate is an intermediate hydrogenation product, the difference in selectivity for the intermediate product can only be reflected when the conversion rate is not zero but close to 100%. Therefore, the reaction space velocity is controlled to achieve a conversion rate of 98.5%.
[0025] The specific experimental conditions for the catalysts in the comparative examples and each embodiment are shown in Table 1 below, and the activity data are shown in Table 2.
[0026] Comparative Example 1 Preparation of copper-silver bimetallic catalysts (without complexing agent, co-impregnation method) This comparative example is the preparation of a copper-silver bimetallic catalyst (comparative sample 1) without the addition of a complexing agent using the co-impregnation method, as detailed below: 0.1032 g of silver nitrate (AgNO3) and 0.6766 g of copper nitrate (Cu(NO3)2∙3H2O) were dissolved in 150 mL of deionized water and stirred at room temperature, protected from light. Then, the corresponding mass of dried fumed silica was slowly added, and the mixture was stirred vigorously for 20 h in the dark. The mixture was then rotary evaporated at 40 °C to remove excess water. The resulting solid was dried in an oven at 110 °C for 15 h and calcined in a muffle furnace at 400 °C for 4 h. The resulting catalyst was reduced in H2 at 300 °C for 4 h before use.
[0027] The comparative catalyst was subjected to the above-described online reduction conditions and catalyst evaluation method for 2.0 h. -1The reaction was carried out under the following conditions, and the catalyst yield values are shown in Table 2.
[0028] Comparative Example 2 Preparation of a copper-silver bimetallic catalyst (using mannitol as a complexing agent via a reduction-displacement method, with a molar ratio of complexing agent to Ag of 2:1). This comparative example uses mannitol as a complexing agent, with the amount of mannitol precisely used to complex silver ions, to prepare a copper-silver bimetallic catalyst, as shown in the preparation of control sample 2. Preparation of copper silicate precursor by ammonia stripping method: Dissolve 6.7677 g of Cu(NO3)2·H2O in 150 mL of deionized water, then add 27.3 mL of 25 wt.% ammonia solution to obtain a copper-ammonia complex solution. After thorough mixing, add 44.5 mL of silica sol and continue aging for 4 h. Subsequently, heat to 80 °C to remove ammonia until the pH drops to 6-7. After filtering and washing the resulting mixed solution with deionized water, dry the sample in an oven at 110 °C for 12 h, then transfer it to a muffle furnace and calcine at 400 °C for 4 h. This yields a 10 wt.% Cu-loaded copper silicate precursor.
[0029] Preparation of copper-silver bimetallic catalysts: First, 1 g of copper silicate precursor was reduced at 300℃ under H2 atmosphere for 4 h. 90 mL of deionized water was added to a three-necked flask, and the system was rinsed with N2 to remove air. The solution was then placed in an ice-water bath, and 1.2590 g of polyethylene glycol (PEG-1000) was fully dissolved before adding the reduced copper silicate precursor. Simultaneously, 0.1032 g of AgNO3 was weighed and dissolved in a small amount of deionized water, and an appropriate amount of ammonia was added to obtain a silver ammonia solution. Then, 0.2213 g of mannitol was added, and the mixture was thoroughly mixed and transferred to a three-necked flask. After reacting in the dark for 30 min, the mixture was filtered and washed with a large amount of deionized water. The resulting sample was dried in an oven at 110℃ for 12 h to obtain the final catalyst. The comparative catalyst was subjected to the above-described online reduction conditions and catalyst evaluation method for 2.0 h. -1 The reaction was carried out under the following conditions, and the catalyst yield values are shown in Table 2.
[0030] Comparative Example 3 Preparation of a copper-silver bimetallic catalyst (using 1,6-hexanediol as a complexing agent via a reduction-displacement method, with a complexing agent to Ag molar ratio of 6:1). This comparative example uses 1,6-hexanediol as a complexing agent, with a molar amount three times that of mannitol in Comparative Example 1, to prepare the copper-silver bimetallic catalyst for Comparative Sample 3, as detailed below: Preparation of copper silicate precursor by ammonia stripping method: Refer to the preparation method of Comparative Example 2.
[0031] Preparation of copper-silver bimetallic catalysts: The preparation method is the same as that of Comparative Example 2. The difference is that 1,6-hexanediol was used as the complexing agent, and the mass of 0.4307 g of 1,6-hexanediol added was 0.4307 g.
[0032] In this embodiment, the catalyst was subjected to the above-described online reduction conditions and catalyst evaluation method for 2.0 h. -1 The reaction was carried out under the following conditions, and the catalyst yield values are shown in Table 2.
[0033] Example 1 Preparation of a copper-silver bimetallic catalyst (using ethylene glycol as a complexing agent via a reduction-displacement method, with a complexing agent to Ag molar ratio of 2:1). In this embodiment, ethylene glycol was used as a complexing agent, and the amount of the copper-silver bimetallic catalyst was 1 times that of mannitol in Comparative Example 1.
[0034] Preparation of copper silicate precursor by ammonia stripping method: Refer to the preparation method of Comparative Example 2.
[0035] Preparation of copper-silver bimetallic catalysts: The preparation method is the same as that of Comparative Example 2. The difference is that ethylene glycol was used as the complexing agent, and the mass of ethylene glycol added was 0.0752 g.
[0036] In this embodiment, the catalyst was subjected to the above-described online reduction conditions and catalyst evaluation method for 2.0 h. -1 The reaction was carried out under the following conditions, and the catalyst conversion, selectivity and product yield are shown in Table 2.
[0037] Example 2 Preparation of a copper-silver bimetallic catalyst (using ethylene glycol as a complexing agent via a reduction-displacement method, with a complexing agent to Ag molar ratio of 6:1). In this embodiment, ethylene glycol was used as a complexing agent, and the amount of the copper-silver bimetallic catalyst was three times that of mannitol in Comparative Example 1 to prepare Sample 2.
[0038] Preparation of copper silicate precursor by ammonia stripping method: Refer to the preparation method of Comparative Example 2.
[0039] Preparation of copper-silver bimetallic catalysts: The preparation method is the same as that of Comparative Example 2. The difference is that ethylene glycol was used as the complexing agent, and the mass of ethylene glycol added was 0.2262 g.
[0040] In this embodiment, the catalyst was evaluated according to the above-described online reduction conditions and catalyst evaluation method. The catalyst evaluation conditions and the values of catalyst conversion, selectivity and product yield are shown in Table 2.
[0041] Example 3 Preparation of a copper-silver bimetallic catalyst (using ethylene glycol as a complexing agent via a reduction-displacement method, with a complexing agent to Ag molar ratio of 18:1). This comparative example uses ethylene glycol as a complexing agent, with a molar amount nine times that of mannitol in Comparative Example 1, to prepare Sample 3 using a copper-silver bimetallic catalyst, as detailed below: Preparation of copper silicate precursor by ammonia stripping method: Refer to the preparation method of Comparative Example 2.
[0042] Preparation of copper-silver bimetallic catalysts: The preparation method is the same as that of Comparative Example 2. The difference is that ethylene glycol was used as the complexing agent, and the mass of ethylene glycol added was 0.6787 g.
[0043] In this embodiment, the catalyst was subjected to the above-described online reduction conditions and catalyst evaluation method for 2.0 h. -1 The reaction was carried out under the following conditions, and the catalyst conversion, selectivity and product yield are shown in Table 2.
[0044] Comparative Examples 1-3 and Examples 1-3 show that the copper-silver bimetallic catalyst prepared by the reduction-displacement method and the addition of a complexing agent can effectively promote the directional anchoring of silver species on the surface of copper species, thereby improving the selectivity of the catalyst for methyl glycolate.
[0045] Comparative Examples 2 and 3 with Example 2 show that when the amount of hydroxyl groups added to the complexing agent is the same, the molecular size and hydroxyl group distribution of the complexing agent have a certain influence on the formation of the core-shell structure. For example, in Comparative Example 2, mannitol has a larger molecular volume, and the arrangement of hydroxyl groups is affected by the molecular conformation, resulting in a lower proportion of hydroxyl groups that can effectively participate in the complexation of silver ions. Therefore, compared with Example 2, the degree of silver species coating is lower. In Comparative Example 3, 1,6-hexanediol has a longer molecular chain, with hydroxyl groups located at both ends of the molecule and a more dispersed spatial distribution. Although this structure can complex silver ions, its larger molecular size and stronger steric hindrance easily hinder the diffusion of silver ions to the copper surface, making it easier for silver species to settle on the silica carrier surface, resulting in a weakening of the intermetallic interaction.
[0046] As can be seen from Examples 1-3, when ethylene glycol with a small molecular size and appropriate hydroxyl distribution is used as a complexing agent, if the amount of hydroxyl added is insufficient, as in Example 1, the number of hydroxyl groups in the system is insufficient to effectively complex silver ions, causing some silver species to nucleate independently and some to agglomerate. If the amount of hydroxyl added is excessive, as in Example 3, although the silver ion complexing ability is enhanced, the excessive ethylene glycol may be adsorbed or remain on the copper surface and in the carrier pores, causing the diffusion of silver ions to the copper surface to be hindered, resulting in some silver species being misaligned and deposited on the carrier silica. In Example 2, the amount of ethylene glycol added is moderate, and the amount of hydroxyl added in the system can effectively complex silver ions, but it is not enough to cause obvious complexing agent residue or strong steric hindrance, so that the silver species can be uniformly deposited and coated on the surface of the copper species to form a relatively complete Cu@Ag core-shell structure.
[0047] Table 1. Preparation conditions and particle size of each catalyst Table 2. Activity data of each catalyst for the heterogeneous hydrogenation reaction of dimethyl oxalate. Table 3 Pore structure properties of each catalyst As shown in Examples 1-3 of Tables 1-3, the total amount of hydroxyl groups added has a significant impact on the catalyst structure and performance. With increasing hydroxyl group addition, the catalyst pore structure changes significantly: pore size and specific surface area decrease. This indicates that excessive addition of complexing agents can lead to complexing agent residue and pore blockage, affecting the catalyst's acidity / basicity and increasing the selectivity of other byproducts.
[0048] Comparative examples and Examples 1-3 in Tables 1 and 2, and... Figure 1 It is evident that catalyst performance is not solely determined by the total amount of hydroxyl groups added. Under the same hydroxyl group addition conditions, Comparative Examples 2 and 3, and Example 2 exhibited different catalytic activities, indicating that the molecular size of the complexing agent and the spatial distribution of hydroxyl groups have a significant impact on the complexation and reduction displacement behavior of silver ions, as well as the formation of the Cu@Ag core-shell structure. Specifically, Example 2 achieved the optimal methyl glycolate yield while maintaining a high dimethyl oxalate conversion rate, demonstrating that small molecular size and a favorable hydroxyl group distribution are key to forming a uniform silver shell.
[0049] The raw materials of this invention are readily available, and the preparation process is mild. The formation of Cu@Ag core-shell structure can be synergistically controlled by the molecular size of the complexing agent, the amount of hydroxyl group added, and the spatial distribution. It can be used in the process of preparing methyl glycolate by hydrogenation of dimethyl oxalate with high selectivity.
Claims
1. A bimetallic catalyst prepared using a complexing agent containing only hydroxyl functional groups, comprising a support and an active component, said active component being a copper species and a silver species, characterized in that: The support is silica; the silver species account for 1-10 wt.% of the total mass of the catalyst, and the copper species account for 1-10 wt.% of the total mass of the catalyst. A copper silicate precursor was prepared by ammonia stripping. The reduced precursor, silver ammonia solution, and complexing agent were mixed and treated to obtain the catalyst product. The complexing agent, ethylene glycol, can complex silver ions, thereby regulating the rate of the electrochemical displacement reaction.
2. The bimetallic catalyst prepared using a complexing agent containing only hydroxyl functional groups according to claim 1, characterized in that: The catalyst has a specific surface area of 50-300 m². 2 / g, with an average pore volume of 0.3-1.7 cm³. 3 / g, with an average pore size of 5.0-15.0 nm.
3. The bimetallic catalyst prepared using a complexing agent containing only hydroxyl functional groups according to claim 2, characterized in that: The catalyst has the following structure: silver species are coated on the surface of a copper core in the form of a shell, forming a core-shell structure; the core-shell structure is located on a support of silicon dioxide in the form of particles, wherein strong interactions are formed between the metals and between copper and silicon dioxide.
4. A bimetallic catalyst prepared using a complexing agent containing only hydroxyl functional groups according to claim 3, characterized in that: The complexing agent has the characteristics of small molecular size, moderate amount of hydroxyl addition and dispersed spatial distribution of hydroxyl groups, which is a complexing agent system that is conducive to the complexation and migration of silver ions.
5. A method for preparing the bimetallic catalyst as described in claim 4, characterized in that: It includes the following steps: Dissolve copper salt in water, add ammonia, stir thoroughly, and then evenly drop the solution into silica sol. After aging treatment, the temperature is raised to evaporate ammonia, followed by cooling, filtration, and washing. The washed product was dried and then calcined at high temperature to obtain a copper silicate precursor, which was then reduced. The precursor, silver salt, and complexing agent are mixed, air is removed from the system, and the mixture is filtered and washed with a large amount of deionized water. After drying, the catalyst product is obtained.
6. The method for preparing a bimetallic catalyst according to claim 5, characterized in that: The aging process lasted for 4 hours, the ammonia stripping temperature was 80℃, and the ammonia stripping process ended when the solution pH reached 6-7.
7. The method for preparing a bimetallic catalyst according to claim 5, characterized in that: The product after washing is dried at a temperature of 80-130 degrees Celsius for 12-24 hours.
8. The method for preparing a bimetallic catalyst according to claim 5, characterized in that: The atmosphere of the mixed system containing copper silicate precursor, silver ammonia solution and complexing agent is nitrogen.
9. A method for preparing a bimetallic catalyst according to claim 5, 6, 7, or 8, characterized in that: The mass ratio of copper to silver is 3:
2.
10. The application of a copper-silver bimetallic catalyst as described in claim 1, 2, 3, 4, or 9, characterized in that: Specifically, the catalyst is used to catalyze the selective hydrogenation of dimethyl oxalate to methyl glycolate. A bimetallic catalyst is packed into a fixed-bed reactor, and gasified dimethyl oxalate feedstock and hydrogen are mixed and then reacted. The reaction pressure was 0.5-3.5 MPa; the reaction temperature was 200-250 ℃; and the mass hourly space velocity (WHSV) of dimethyl oxalate was 0.1-6.0 h⁻¹. -1 The hydrogen-ester molar ratio is 60-140.